From Rebels to Rulers: The Challenges of Transition for Non-state Armed Groups in Mindanao and Myanmar - South A. (2017)
© 2016 BCAS, Inc. ABSTRACT: This article presents a critical comparison of the ongoing peace processes in the southern Philippines and Myanmar (Burma). It does so by examining two key armed groups: the Moro Islamic Liberation Front (MILF) on Mindanao, and the Karen National Union (KNU) in Myanmar. We identify common elements that help to explain the relative – albeit incomplete – success of these two groups in navigating their respective peace processes. The MILF and KNU are ethnonationalist armed groups struggling for self-determination against states that are experienced by ethnic minority communities as culturally alien, and economically and politically dominant. Both conflict actors are characterized by complex combinations of “greed” and “grievance” factors but nevertheless enjoy significant (albeit contested) political legitimacy among the communities they seek to represent. We explore the complex relationships between armed ethnic groups, conflict-affected communities, and civil society actors. We argue that engagement with civil society is a key element of success in the Mindanao peace process, which could be replicated in Myanmar. We examine the roles and changing nature of the state in the Philippines and Myanmar, and contrast the degrees of international involvement, as key variables in these peace processes. We observe that negotiations of comprehensive peace settlements are threatened by “the tyranny of elections” in Myanmar (2015) and the Philippines (2016), and observe the importance of including national parliaments in peace processes in a timely manner. The peace process between Manila and the MILF represents a rare example of a Muslim minority pursuing its political objectives through structured dialogue. The article focuses on the challenges faced by armed groups moving from insurgency to reinvent themselves as credible political actors and governance authorities. Our analysis draws on peace-building literature, specifically the phenomenon of “rebel governance.”